Hypothalamic lesions increase saline ingestion induced by injection of angiotensin II into AV3V in rats - De Arruda Camargo, L. A. [UNESP]; Saad, W. A. [UNESP]; Renzi, A. [UNESP]; De Luca, L. A. [UNESP]; Goncalves, J. R. [UNESP]; Menani, J. V. [UNESP] (My University, 1991)
Water and 3% NaCl intake were increased by the injection of 4 ng angiotensin II (ANG II) into the anteroventral third ventricle (AV3V) region of rats. Pretreatment with two specific ANG II receptor antagonists, [octanoyl-Leu8]ANG II and [Leu8]ANG II, significantly reduced ANG II-induced water and saline intake. This inhibition lasted ~30 min, with partial recovery at 60 min. In rats with electrolytic lesion of the bilateral ventromedial nucleus of hypothalamus (VMH), the effect of ANG II on water intake was not different from that observed in sham rats, but saline ingestion increased. In summary, the present results show that the AV3V region is an important central structure for ANG II-induced saline ingestion. Lesion of the VMH increases the response to ANG II, showing an interaction between the AV3V region and the VMH in the regulation of salt ingestion.
Keywords: Angiotensin II antagonists; Salt ingestion; Water ingestion